Development of a Risk-stratified Approach for Follow-up Imaging After Percutaneous Thermal Ablation of Sporadic Stage One Renal Cell Carcinoma - Dreyfuss, Leo D.; Wells, Shane A.; Best, Sara L.; Hedican, Sean P.; Ziemlewicz, Timothy J.; Lubner, Meghan G.; Hinshaw, J. Louis; Lee, Fred T.; Nakada, Stephen Y.; Abel, E. Jason (Urology (Ridgewood, N.J.), 2019)
To analyze risk factors and patterns of RCC recurrence following percutaneous ablation for stage 1 tumors and develop risk-stratified follow-up imaging protocols. Biopsy-proven sporadic stage 1 RCC patients treated with percutaneous microwave ablation (MWA) or cryoablation (CA) from 2002 to 2017 were included. Kaplan-Meier analysis was used to estimate local and distant recurrence-free survival, cancer-specific survival and metastatic-free survival. Multivariable models were used to identify risk factors associated with recurrence. A total of 256 patients with stage 1 RCC (215 T1a, 41 T1b) were treated with percutaneous MWA (178 subjects) or CA (78 subjects). Recurrence was identified in 23 patients (16 local, 7 distant). Clinical T stage (HR 2.46, 95% CI 1.06-5.72, P = .04) and tumor grade (HR 4.17, 95% CI 1.17-14.76, P = .03) were independent predictors of recurrence. Recurrence was not associated with Nephrometry score, cystic tumors, ablation modality (CA vs MWA) or gender. Five-year cancer-specific survival, and metastatic-free survival were 98.6% and 97.4%, respectively. Patients were stratified into 2 groups: reduced risk stage 1 (no risk factors) or elevated risk stage 1 (≥1 risk factor). Recurrence risk was higher in the elevated-risk group (HR = 3.19, 95% CI 1.35-7.53, P = .008). Five-year overall recurrence-free survival (local + distant) was higher in reduced-risk vs elevated-risk cohorts, 88% vs 69%, P = .005. High nuclear grade or T1b tumors have increased recurrence risk following percutaneous thermal ablation for stage 1 RCC. Current postablation follow-up protocols may be modified for individual recurrence risk to allow more frequent imaging for elevated-risk patients, while enabling less frequent imaging for reduced-risk patients.